Leadership Soft Skills and Success Factors Affecting to Development of Quality and Standard of Primary Health Care Services in Health Service Unit for The Directors of Sub-District Health Promoting Hospital, Buriram Province - Heebkaew, ่๋Jetsadakorn; Prasit, ืNakarin; Yanarueng, Supachai (Journal of The Royal Thai Army Nurses, 2025)
This cross-sectional descriptive study aimed at examining leadership soft skills and success factors affecting to development of quality and standard of primary health care services in health service unit for the directors of sub-district health promoting hospital, Buriram province, The study was based on 165 Sample size by used simple random sampling. The content validity of the questionnaire was verified by three experts. Data was collected between 1-31 January 2024. The statistics used to analyze the data were descriptive statistics. and inferential statistics, including Pearson correlation coefficient and stepwise multiple linear regression. The results showed that overall leadership soft skills and success factors had a high relationship with the development of the quality and standards of primary health services in the health service units (r= .779, p-value< .001) (r= .778, p-value< .001) In addition, the results found that planning and organizing skill, creating understanding for collaboration among stakeholders at all levels, having supportive plans for organizational units, developing and teaching skills, receiving support from managers at all levels, communication skills can together predict the development of quality and standards of primary healthcare services in the health service unit of the director of a district hospital in Buriram province were at 72.0% ( = .720).